2011
DOI: 10.4269/ajtmh.2011.11-0030
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Establishing the Correct Diagnosis of Outbreaks of Acute Febrile Illnesses in Africa: The Case of a Likely Brucella Outbreak among Nomadic Pastoralists, Northeast Kenya, March–July 2005

Abstract: Acknowledgments: We thank the Ministry Of Health, Provincial Medical Office, Northeastern Province Kenya and Liboi area community leaders who assisted in this investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…61,62 However, we did find that participants with brucellosis were more likely to have other bacterial zoonoses compared with participants without brucellosis. Although this may be caused by serologic cross-reactivity, prior studies have also shown co-infections with other zoonoses among patients with brucellosis, 37,63 suggesting shared risk factors for these infections.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…61,62 However, we did find that participants with brucellosis were more likely to have other bacterial zoonoses compared with participants without brucellosis. Although this may be caused by serologic cross-reactivity, prior studies have also shown co-infections with other zoonoses among patients with brucellosis, 37,63 suggesting shared risk factors for these infections.…”
Section: Discussionmentioning
confidence: 93%
“…However, it is notable that no association between brucellosis and rural residence, weekly expenditures, or paternal tribe was identified. Brucellosis has been well documented among nomadic pastoralists in sub-Saharan Africa, 16,22,37,38 and these populations are generally thought to be at increased risk for contracting brucellosis because of their close contact with livestock. 22 However, some studies have suggested a recent shift in the epidemiology of brucellosis from rural to urban settings, possibly related to unpasteurized milk consumption in urban environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first human cases were reported in 1977, 16 and in 2011 a study investigating acute febrile illnesses in northern Kenya reported cases of leptospirosis. 17 This study examined slaughterhouse workers in western Kenya for serological evidence of exposure to Leptospira spp. and identified risk factors associated with seropositivity in this population.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…This province was selected because public health support and disease surveillance have been extremely limited and outbreaks of re-emerging diseases have been reported [15], [19], [20]. The study design was described in detail elsewhere [12].…”
Section: Methodsmentioning
confidence: 99%